Baetis majus sp. nov., new species of mayfly (Ephemeroptera: Baetidae) from Far East of Russia - Tiunova, Tatiana M.; Semenchenko, Alexander A.; Tong, Xiaoli (Zootaxa, 2021)
A new species, Baetis majus Tiunova sp. nov., is described and illustrated based on larvae and reared adults discovered in the Russian Far East. The differential identification of this species was determined by the characteristics of other representatives of the genus Baetis Leach, including subgenera Baetis Leach and Tenuibaetis Kang & Yang from Eastern and Western Palaearctic, Nearctic and Oriental regions. In addition to morphological studies, DNA barcoding of the described species with average intraspecific K2P distances to nearest neighbours is documented. We reconstructed the phylogenetic relationships of all available cytochrome c oxidase subunit I (COI) sequences of the subgenera of Baetis and Tenuibaetis from four regions. Bayesian analysis using 47 morphological characters additional to partial COI sequences did not allow to determine the species-group of the Baetis genus to which the described species belongs.